2002
DOI: 10.1097/00004356-200209000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Daily hassles and stress vulnerability in patients with a whiplash-associated disorder

Abstract: Daily hassles and stress vulnerability in patients with a whiplash-associated disorderBlokhorst, M.G.B.G.; Lousberg, R.; Vingerhoets, Ad; Winter, F.A.M.; Zilvold, G. General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
10
1
Order By: Relevance
“…Although it is reasonable that physical trauma has a role in the expression of disability secondary to WADs, 11 it is also becoming increasingly clear that psychosocial factors, as well as compensation systems and medicolegal factors, may also contribute in many cases. [7][8][9][10][11][12][13]24 Our analysis of WAD type II patients in receipt of compensation and undergoing similar treatment from the same chiropractor found that higher self-reported disability on initial assessment was associated with female sex and in particular by retaining a lawyer. Large prospective studies are needed to establish the validity of these findings.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is reasonable that physical trauma has a role in the expression of disability secondary to WADs, 11 it is also becoming increasingly clear that psychosocial factors, as well as compensation systems and medicolegal factors, may also contribute in many cases. [7][8][9][10][11][12][13]24 Our analysis of WAD type II patients in receipt of compensation and undergoing similar treatment from the same chiropractor found that higher self-reported disability on initial assessment was associated with female sex and in particular by retaining a lawyer. Large prospective studies are needed to establish the validity of these findings.…”
Section: Resultsmentioning
confidence: 99%
“…25 Furthermore it has been concluded that coping and psychological stress responses play an important role in the maintenance or worsening of whiplash-associated complaints. 26 On the other hand there are studies which show that measures of pre-accident psychological status do not predict the physical outcome of whiplash injury. 5,27 In our study we estimated the role of possible depression by using BDI and the role of possible psychic distress by using GHQ, both generally used and accepted validated questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…Validity- EPCL scores correlate positively with distress, and EPCL scores directly influence subjective health complaints, immune activity and cardiovascular function 41,42 …”
Section: Tablementioning
confidence: 99%